2013
DOI: 10.1364/oe.21.030796
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic plasmonic Cu nanoparticles in sol-gel oxide nanopillars studied by spectroscopic Mueller matrix ellipsometry

Abstract: Broadened plasmon resonances of Cu nanoparticles in nanopatterned mixed oxide sol-gel nanopillars are shown to be readily detected by spectroscopic Mueller matrix ellipsometry. The plasmonic nanomaterials are obtained by low energy ion sputtering of a CuO sol-gel film. Both s- and p-polarized plasmon resonances are observed in the off-block-diagonal and the block-diagonal Mueller matrix elements as well as in the generalized ellipsometric parameters. The resonant features in all elements correlate with both ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…parallel to the glass surfaces). [36][37] Indeed, the anisotropic host matrix can also make a small shift in the Frolich/Mie resonance condition [36][37] , but the amplitudes of the peaks in ψ small compared to the cases with particle anisotropy. Note that the attenuation described by α p conveys both a component perpendicular and parallel to the sample surface, and its magnitude is also dependent on path length, both dependent on incidence angle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…parallel to the glass surfaces). [36][37] Indeed, the anisotropic host matrix can also make a small shift in the Frolich/Mie resonance condition [36][37] , but the amplitudes of the peaks in ψ small compared to the cases with particle anisotropy. Note that the attenuation described by α p conveys both a component perpendicular and parallel to the sample surface, and its magnitude is also dependent on path length, both dependent on incidence angle.…”
Section: Resultsmentioning
confidence: 99%
“…This signal can be either a result of a modulation of the Fresnel coefficients at the interfaces which was measured to be a weak effect through reection ellipsometry, or a result of an anisotropic host matrix. 36,37 Indeed, the anisotropic host matrix can also make a small shi in the Frolich/Mie resonance condition, 36,37 but the amplitudes of the peaks in j are small compared to the cases with particle anisotropy. Interestingly, such an optical anisotropy in the host matrix can be envisaged locally around e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A unique feature of plasmonic metasurfaces is that their far-field scattering provides key information regarding their near-field properties, paving the way toward harnessing their polarization properties for device applications. In addition to optical devices, , depolarization observed in the far-field scattering plays an important role in sensing applications, far-field diagnosis, and in the general functionality of metasurfaces. ,, Previous studies have shown that a metasurface platform based on high-contrast dielectric elliptical nanoposts can provide a high degree of control of polarization and phase with subwavelength spatial resolution . Additionally, the possibility of imposing phase profiles also offers new opportunities for metasurface polarization optics …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] For example, metallic Cu nanopillars or nanoparticles in an oxide matrix have been reported for plasmon resonance studies and for battery electrodes. [20][21][22] The vertical nanocomposite fi lms reported to date comprise two different phases, but additional functionalities and crosscoupling of properties may be possible in nanocomposites with more than two phases. Three-phase oxide nanocomposites consisting of La 2 O 3 , SrO, and Co 2 O 3 were reported previously [ 23,24 ] but there has been no report on three-phase nanocomposites showing a vertically oriented epitaxial growth analogous to that seen in two-phase nanocomposites.…”
mentioning
confidence: 99%